Casual role of infectious agents in cancer: An overview - Jila Masrour-Roudsari; Soheil Ebrahimpour (Babol University of Medical Sciences, 2017)
Cancer is a complex group of diseases with multiple eventual causes. The underlying causes are not fully known. Thus, learning more about the known causes of cancer is an important issue. Moreover, among these factors, infection and its association to cancers is controversial. Although, it seems that the genome instability of the cells can initiate cancer development. The purpose of this review was to present the role of infection in the development of cancer. Infectious agents, such as hepatitis B (HBV) and C viruses (HCV), Epstein-Barr virus (EBV), human papillomavirus (HPV), human immunodeficiency virus type 1 (HIV-1), Helicobacter pylori (H. pylori) and Streptococcus bovis (S. bovis)  contribute to the pathogenesis of different cancers. These cancers include hepatocellular carcinoma, Burkitt's lymphoma, nasopharyngeal carcinoma, cervical cancers, non-Hodgkin lymphoma, Kaposi sarcoma, adenocarcinoma and lymphoma. Screenings of infectious diseases in cancer patients may open up areas of research in the identification of optimizing cancer control strategies.